Manajemen Pembelajaran Bahasa Inggris Melalui Platform Online Sederhana Pada Pondok Pesantren Riyadus Sholihin - Puspa Fortuna Zulfa; Husnir Faqih; Ery Suryanti (LPPI UMN AL WASHLIYAH, 2025)
English Language Learning Management for Students Using a Simple Online Platform at the Riyadush Sholihin Islamic Boarding School aims to improve students' English skills through the effective use of digital technology. This activity is designed to help students master English with interactive and contextual methods, utilizing simple online platforms such as YouTube and WhatsApp. The YouTube platform is used to present learning videos in the form of Islamic vocabulary, stories of the Prophet in English, and everyday conversations with an Islamic context, also providing alternative channels that can be used for English learning in the classroom to be more varied and interactive. Meanwhile, the WhatsApp group is used as an interactive discussion space, where students can ask questions and practice directly with teachers who can also provide additional materials related to English learning to enrich students' knowledge. The problems faced by this Islamic boarding school are that the use of technology in learning is still lacking, English learning still uses conventional methods, limited access and knowledge of digital learning resources, and a lack of interactive media in language learning. Learning is designed to suit the time and needs of students without disrupting their prayer schedules and religious activities. In addition to implementing a simple platform, this program will also provide the necessary digital references and resources related to the use of interactive media in English learning for students.